A 15-Minute Documentary about ‘Cyber-Mobbing’. From creating the concept to the finished film - Vera Müller (2017)
Creating a documentary is an art form I had not experienced before, but the weight of emotions and the affects a documentary can have fascinated me and I wanted to further explore this exciting genre as my bachelor thesis early on. I chose ‘Cyber- Mobbing’ as subject because it is a relatively new problem our society has to deal with. I first came in contact with it working on a Talk show about contemporary social issues. The work there and the scope of what I learned each episode got me interested in creating awareness for problems as such as ‘Cyber-Mobbing’. Having nieces and nephews of my own I am very invested in learning of any harm that could come to them. As common as ‘Cyber-Mobbing’ has become and the fact that it mostly replaced ‘classic Mobbing’ in the schoolyard, it would surprise me to learn any of the children I know had already experienced it. My objective for this documentary was to create awareness and give people information on how to properly deal with the subject of ‘Cyber-Mobbing’.